Characterization of thermostable carboxypeptidase from high-altitude hot spring metagenome - Wani, Atif Khurshid; Chopra, Chirag; Ansari, Mushtaq Ahmad; Dar, Mudasir A.; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Singh, Reena (Elsevier, 2024)
This study explored the metagenome of the Pir Panjal Hot Spring (PPHS) to identify thermostable hydrolases. The carboxypeptidase (CarP) gene was successfully amplified and cloned into Escherichia coli DH5-α cells, followed by expression in E. coli BL21-DE3 cells. The CarP enzyme was comprehensively characterized in vitro. Sequencing analysis revealed an open reading frame encoding a functional protein of 504 amino acids, with a molecular weight of 58.65 kDa and an isoelectric point of 4.81. The CarP protein was purified using Ni-His affinity chromatography, and the experimental molecular weight matched in silico predictions. The enzyme exhibited significant thermostability and alkaliphilic properties, with optimal activity at 70 °C and pH 10.0. Additionally, the presence of Zn+2 ions at concentrations of 5 and 10 mmol/L enhanced protease activity by 1.4 and 1.5-fold, respectively. This study reports the discovery of a novel, multifunctional, and thermostable CarP from hot-spring metagenomes. The enzyme's stability against high temperatures, metal ions, surfactants, and inhibitors, along with its specific substrate interactions, highlights its potential for various biotechnological applications.
Keywords: Enzymes; Hydrolases; Metagenomics; Protease; Thermostable